Motivasi Berolahraga Zumba Pada Wanita: Studi Survei Online - Indra Prawobo; Yudy Hendrayana; Amung Ma’Mun; Berliana Berliana; Edi Setiawan (Jurnal MensSana, 2022)
Zumba is a form of sport or dance originating from Brazil that has energetic movements accompanied by music, but in the current era of the COVID-19 pandemic, it is estimated that there is a decrease in motivation to do Zumba. Therefore, the purpose of this study was to conduct a survey about how much motivation women have in doing Zumba exercises. This research is a descriptive study based on an online survey. The women who are members of the style studio used as samples in this study were 22 participants using a complete sampling technique. The instrument in this study used a questionnaire. The research instrument adopted from the sport motivation scale. Surveys with data collection procedures using questionnaires were used in this study. The frequency distribution technique was used in the data analysis, along with the calculation of the percentage. The findings in this study indicate that women's motivation to exercise Zumba is quite good, as evidenced by the percentage value of 32%. Thus, the study concludes that women still have a good enough motivation to do Zumba even during the COVID-19 pandemic crisis